2005
DOI: 10.1016/j.febslet.2005.05.059
|View full text |Cite
|
Sign up to set email alerts
|

DNA‐binding proteins of the Whirly family in Arabidopsis thaliana are targeted to the organelles

Abstract: Arabidopsis thaliana contains three genes with high homology to potato p24 which was described as a member of the Whirly family of nuclear transcriptional activators. Computer-based analysis revealed that all Arabidopsis Whirly (Why) proteins contain targeting sequences for either plastids or mitochondria. The functionality of these sequences was demonstrated by in vitro import assays into isolated organelles. Transient expression of GFP fusion proteins in protoplasts and onion epidermal cells confirmed the lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
126
1
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 110 publications
(135 citation statements)
references
References 22 publications
1
126
1
1
Order By: Relevance
“…Furthermore, pTAC1 and pTAC11 exhibit striking similarities to p24 proteins, which are members of the Whirly proteins of nuclear transcription factors (Desveaux et al, 2002(Desveaux et al, , 2004. All Whirly proteins have target sequences for organelles (Krause et al, 2005); thus, they might be dually targeted to the nucleus and the plastid. The exact functions of the pTAC proteins remain to be determined; however, the striking similarities of the observed phenotypes of the knockout lines for three of these proteins with those of Drpo mutants and other mutants impaired in PEP function suggests that they are also involved in plastid gene expression.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, pTAC1 and pTAC11 exhibit striking similarities to p24 proteins, which are members of the Whirly proteins of nuclear transcription factors (Desveaux et al, 2002(Desveaux et al, , 2004. All Whirly proteins have target sequences for organelles (Krause et al, 2005); thus, they might be dually targeted to the nucleus and the plastid. The exact functions of the pTAC proteins remain to be determined; however, the striking similarities of the observed phenotypes of the knockout lines for three of these proteins with those of Drpo mutants and other mutants impaired in PEP function suggests that they are also involved in plastid gene expression.…”
Section: Discussionmentioning
confidence: 99%
“…Examples are PEND, CND41, PD1, PD3 (Kodama 2007) as well as Whirly1 (Krause et al 2005;Grabowski et al 2008) and the newly identified ptNAP SWIB-4 (Melonek et al 2012). It has been suggested that these proteins have changed their subcellular localization during evolution and became plastid or dually targeted proteins.…”
Section: Bifunctionality and Dual Targeting Of Ptnapsmentioning
confidence: 99%
“…van Wijk, unpublished data). Plastid pTAC11 is a member of the Whirly family of multifunctional RNA-and DNA-binding proteins located in mitochondria and plastids (Krause et al, 2005). Members of the Whirly family are involved in organelle genome stability and quality control and, perhaps, RNA metabolism (Prikryl et al, 2008;Maréchal et al, 2009;Cappadocia et al, 2012).…”
Section: Effects On Plastid Gene Expression and Protein Homeostasismentioning
confidence: 99%